Comprensión lectora y pensamiento crítico en estudiantes del quinto grado de secundaria Institución Educativa Mariscal Oscar Raimundo Benavides, Iquitos 2022 - Ruiz Rodriguez, Fridyt (2023)
The objective of the study was: To determine how reading comprehension is related to critical thinking in fifth grade students of an Educational Institution in Iquitos 2022. The study was confirmatory, with a correlational and transactional design, made up of a population of 532 students. and a sample of 224 subjects; Two tests were used to evaluate the study variables. The results in reading comprehension revealed that 9.8% of respondents reported an outstanding level of comprehension; 14.3% an expected level of achievement; 44.6% in process; 31.3% at the beginning. Regarding critical thinking, it was determined that 9.8% of respondents reported a high level; 44.6% an average level; and 36.6% a low level. The results of the inferential analysis allowed us to determine that there is a significant relationship between reading comprehension and the four dimensions of critical thinking, dimension: analyzes information (rs=0.591) (0.000%); dimension: infers implications and/or consequences (rs=0.589) (0.000%); dimension: proposes alternative solutions (rs=0.639) (0.000%); and in the dimension: he argues his position (rs=0.536) (0.000%). It is concluded that reading comprehension is significantly related to critical thinking in students of the study sample (rs = 0.690) (0.000%), approving the general and specific research hypotheses formulated.